4分之1=12分之(3 )=36分之( 9)=(28 )分之7=(0.25 )
4分之1=12分之( )=36分之( )=( )分之7=( )
1个回答
相关问题
-
36分之1÷(4分之1+12分之1-18分之7-36分之1)+(4分之1+12分之1-18分之7-36分之1)÷36分之
-
(9分之7-4分之1+12分之5)÷36分之1
-
36x(9分之7-12分之5)= 15分之14÷7+7分之1x15分之1 (7分之3+4分之3)x28+7分之4
-
X+6分之5=2分之7+4分之1 X-4分之3=3分之2 9分之7-X-9分之1=5分之2 X+12分之1=36分之7-
-
()÷()=9分之5=36分之()=()分之25=()分之100 4分之1-6分之1=12分之()-12分之()=()
-
( -4分之3-9分之5+12分之7)除以36分之1怎么解
-
(-36分之1)除以(12分之5—9分之7—3分之2)
-
(-12分之7-6分之5+8分之9-4分之3)×(-36)=?
-
-36分之1/[-9分之1+12分之1-18分之1+36分之1
-
35分之15○36分之12 12分之4○15分之6 16分之4○21分之7 21分之3○25分之5 50分之5○200分